Transient Left Ventricular Outflow Tract Obstruction in an Elderly Patient Admitted with Takotsubo - Waleed Khalid Abdullatef; Khaled Al Khodari; Smitha AnilKumar (Heart Views)
A 68-year-old elderly individual presented with takotsubo cardiomyopathy, and echocardiography revealed left ventricular outflow tract obstruction with a substantial gradient, particularly exacerbated by the Valsalva maneuver. Resolution occurred within a few days through meticulous fluid management and beta-blocker administration, concurrent with an improvement in ejection fraction.